Antimicrobial Step-Down Therapy versus Conventional Antimicrobial Therapy in the Treatment of Patients with Sepsis. (31st August 2022) - Peng, Zhuo; Niu, Zequn; Zhang, Rui; Pan, Longfei; Feng, Hui; Zhou, Yang; Pei, Honghong
Abstract : Objective . This study was to evaluate the efficacy of antimicrobial step-down therapy versus conventional antimicrobial therapy in the treatment of patients with sepsis. Methods . Between September 2020 and September 2021, 65 patients with sepsis treated in the intensive care unit (ICU) of our hospital were recruited and assigned at a ratio of 1 : 1 to receive either conventional antimicrobial therapy (sulbactam plus cefoperazone) (control group) or antimicrobial step-down therapy (imipenem/cilastatin) (observation group). The results of drug sensitivity tests and clinical effects were evaluated comprehensively after 3-5 d of treatment, downgraded, and upgraded, or maintenance treatment was administered for 10 d. Outcome measures included clinical and laboratory indices and treatment efficacy. Results . Antimicrobial step-down therapy resulted in a significantly higher efficacy and lower levels of white blood cell (WBC) count and C-reactive protein (CRP) versus conventional antimicrobial therapy (P < 0.05 ). The patients given antimicrobial step-down therapy showed a significantly shorter duration of antimicrobial drug administration, temperature recovery, time of respiratory support, and ICU stays versus conventional antimicrobial therapy (P < 0.05 ). Conclusion . Antimicrobial step-down therapy contributes to the mitigation of inflammatory responses in patients with sepsis and shortens the duration of antimicrobial drug use and ICU stay versus conventional antimicrobial therapy. The reliability of the conclusions can be further increased if multicenter and large sample clinical observations can be conducted, which is the direction of endeavor for future clinical studies.